Subwavelength resonant dielectric nanoparticles with high refractive indices. (18th July 2019) - Ammari, Habib; Dabrowski, Alexander; Fitzpatrick, Brian; Millien, Pierre; Sini, Mourad
Abstract : This paper aims at understanding the nature of the subwavelength resonant frequencies of dielectric particles with high refractive indices. It is proved that for an arbitrary shaped particle, these subwavelength resonant frequencies can be expressed in terms of the eigenvalues of the Newtonian potential associated with its shape. The enhancement of the scattered field at the resonant frequencies is shown. The hybridization of the subwavelength resonant frequencies of a dimer consisting of high refractive index dielectric nanoparticles is also characterized.